Determination of Residues of Endosulphan and its Metabolites in Spinach - Wadaskar, J.V.; Ekhe, J.D. (Asian Journal of Chemistry, 2012)
Endosulphan is non-systemic insecticide and acaricide with contact and stomach action. It is widely used on various vegetable crops. Time period between the last spray on the vegetables and its consumption by the customer is often much shorter than that of the other crops like wheat, rice, pulses, grains etc. Therefore, the studies on residual endosulphan have been carried out on spinach in the climatic conditions of Nagpur city. Residues and metabolites of endosulphan were extracted from plant samples and determined using gas chromatography. Normal dose showed negligible residues but higher doses showed the concentration of residues shifting towards MRL (maximum residual limit) values.